PENYULUHAN EDUKASI TANDA-TANDA DEHIDRASI PADA ANAK DENGAN DIARE - Martawinarti, Rts Netisa; Oktaria, Rina; Tri Andini, Febri; Wahyuni, Tri (STIKES Garuda Putih, 2023)
Background: Diarrhea is still a public health problem in developing countries like Indonesia. Mortality studies and basic health research from year to year show that diarrhea is still the main cause of death for children under five in Indonesia. Purpose: Increase public knowledge about the signs of dehydration in children with diarrhea. Method: This education is carried out using a lecture method based on interactive communication. The audience was 25 mothers who had children under five. Pre- and post-test questionnaires were used to evaluate participants' knowledge of diarrhea. Results: before being educated, the pre-test results showed that 64% of participants had fairly good knowledge, and after being given education, participants experienced an increase in knowledge with post-test results of 96%. Conclusion: Health education or education can increase the knowledge of mothers who have toddlers about diarrhea and can be a reference for mothers in taking a stance when their child experiences diarrhea at home.